ANALISIS KESIAPAN PENGGUNAAN SISTEM INFORMASI MANAJEMEN PUSKESMAS (SIMPUS) DALAM PENERIMAAN PASIEN RAWAT JALAN DI UPT PUSKESMAS PULAU GADANG - Tonis, Marian; Maura, Latisa Shafa Maura; Yuliana, Anastasya Shinta (LPPM Universitas Awal Bros, 2023)
The public health center information system is arrangement that provides information to make assist the decision process in carrying out health center management. Based on the results of limited interviews, in 2015 the technical implementation unit of the Pulau Gadang community health center had used a generic regional health information system but was not run again because many tools were damaged and not found, then withdrawn by the Health Office. The purpose of the study was to find out about the readiness of the use of public health center management information systems in outpatient admissions at the technical implementation unit of the Pulau Gadang community health center. This research uses qualitative research with an analytical descriptive approach and uses the Content Analysis model, with a total of 6 informants. The research was conducted using in-depth interviews, observation and document review. The results showed that in general, the technical implementation unit of the public health center of Pulau Gadang was not ready to use the management information system of the public health center because there were still shortcomings in the Man variable, there was no training on the management information system of the public health center and there was no information technology (IT) officer, in the Money variable, there was no budget for the implementation of the management information system of the public health center, on the Material variable, the registration counter facilities are not complete, on the Machine variable, the laptop/computer at the registration counter is not effective because it has not been integrated with the public health center management information system and the printer is in another room, then on the Methods variable, there is no official letter from the Health Office for the obligation to use the public health center management information system and the patient registration SOP is not displayed at the registration counter. Suggestions in this study are the addition of information technology (IT) officers to operate the puskesmas management information system, special training on the puskesmas management information system for registration counter officers, budgeting funds for the implementation of the puskesmas management information system, using queue numbers during outpatient registration, the need for additional machines/facilities at the registration counter such as laptops/computers and printers, displaying patient registration SOP at the outpatient registration counter.